ISSUES OF IMPROVING THEORETICAL FOUNDATIONS AND PRACTICAL MECHANISMS OF THE STRATEGIC MANAGEMENT SYSTEM IN EFFECTIVE ORGANIZATION MANAGEMENT (Eureka Journal of Business, Economics & Innovation Studies, 2026)
This article examines the widening gap between classical strategic management theory and the operational realities facing organizations in 2026. The research objective is twofold: first, to identify structural weaknesses in prevailing theoretical frameworks when applied to digitally interconnected, fast-moving markets; second, to propose practical mechanisms that bridge theory and execution. The methodology combines a critical literature review of foundational and contemporary strategic models with an analysis of emergent organizational practices, including AI-driven analytics, ESG integration, and Agile strategic planning. Key findings indicate that organizations achieving sustained competitive advantage are those that treat strategic management not as a periodic planning exercise but as a continuous, data-informed, adaptive system. The article concludes with a step-by-step implementation framework that synthesizes established analytical tools (SWOT, PESTEL, Balanced Scorecard) with modern digital capabilities.
Keywords: Strategic Management, Digital Transformation, ESG, Agile Strategy, Resource-Based View, Competitive Advantage